Respostas

2014-07-23T16:25:50-03:00
Olá, Matiaslima13!

(x+2)(x+6) = 140
x² + 6x + 2x + 12 = 140
x² + 8x + 12 - 140 = 0
x² + 8x - 128 = 0

a = 1
b = 8
c = -128

Δ = 8² - 4.1.(-128)
Δ = 64 + 512
Δ = 576

-b +- √Δ / 2.a
-8 +- √576 / 2.1
-8 +- 24 / 2

x' = -8+24/2 = 16/2 = 8
x'' = -8-24/2 = -32/2 = -16
2014-07-23T16:30:24-03:00
(x² + 6x + 2x + 12) = 140
x² + 8x + 12 = 140
x² + 8x = 140 - 12
x² + 8x = 128
x² + x = 128/8
x² + x = 16
x + x = 16^2
2x = 4
x = 4/2
x = 2
desculpem-me, mas a resposta está errada, esqueci que era necessário o uso do Bhaskara